Construction and psychometric values of MWT questionnaire - the method of measuring attitudes and value hierarchy in love between a man and a woman - Kapuściński, Marcin (Studia Psychologica: Theoria et praxis, 2007)
This article presents a method of measuring love, based on analysis of values and attitudes heterosexual partners towards each other. Theoretical foundations, the process of creating the method and psychometric values are discussed. Based on results of explorations of three examined groups (77 high school pupils, 166 psychology students, 274 psychology students) some/few bonds with other psychological variables are presented.